2021
DOI: 10.1177/1354856521990246
|View full text |Cite
|
Sign up to set email alerts
|

Media as the great emancipators? Exploring relations between media repertoires and cultural participation in Flanders

Abstract: Media convergence has afforded users an increasing amount of options regarding the media they consume, available at the click of a button. This has led some to clamor about the potential for media to bridge previously existing inequalities and decrease social stratification not just in media use, but in other realms of society as well. Skeptics have argued that while the convergence of media has given users more options in their own media repertoire, social stratification persists. Moreover, if media do increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…This finding shows that ambidexterity (Jenkins & Nielsen, 2020), namely an organization's ability to carry out multiple focuses and build synergies between the two focuses, takes various forms. Therefore, the results of this qualitative and quantitative data analysis support previous findings through interviews (Finneman et al, 2021;Sjøvaag & Krumsvik, 2018) and surveys (Vandenplas & Picone, 2021) that strategies to maintain the viability of printed newspapers take various forms. Moreover, these findings support recent research on the future of the media industry, which found that the future media will have two scenarios: public-serving and businessoriented media (Sjøvaag & Krumsvik, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding shows that ambidexterity (Jenkins & Nielsen, 2020), namely an organization's ability to carry out multiple focuses and build synergies between the two focuses, takes various forms. Therefore, the results of this qualitative and quantitative data analysis support previous findings through interviews (Finneman et al, 2021;Sjøvaag & Krumsvik, 2018) and surveys (Vandenplas & Picone, 2021) that strategies to maintain the viability of printed newspapers take various forms. Moreover, these findings support recent research on the future of the media industry, which found that the future media will have two scenarios: public-serving and businessoriented media (Sjøvaag & Krumsvik, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…They do not have social media accounts. Their proportion of the population is 18.7% (Vandenplas & Picone, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In our own research into media repertoires and cultural participation in Flanders (Vandenplas and Picone 2021), we find a structural homology between both: people with broader media repertoires exhibit a similar openness to participating in cultural activities, and repertoires tailored to highbrow media exhibit a similar preference for highbrow cultural activities. Likewise, could it be that the openness one features in his or her news repertoire is reflected in one's openness regarding key societal issues?…”
Section: News Repertoires Socio-economic Status and Views On The Worldmentioning
confidence: 84%
“…This section presents a methodology for measuring the impact factors of citizen engagement with short-form video entertainment. The most common approach with popular social media is based on negative binomial regression [35], which quantifies the extent of heterogeneity represented by dispersal data once performance metrics are available. This technique could be complemented by the interaction of variables that give rise to simultaneous changes [36] so that the dependency of one variable on the value of another could be interpreted.…”
Section: B Variable Selection and Operationalizationmentioning
confidence: 99%